Short Video in Improving Students’ Writing on Procedure Text: An Experimental Study for Students in Vocational School - Hery Nuraini; Yayat Ruhiat; Lukman Nulhakim (South Sulawesi Education Development (SSED), 2024)
Mastering English skills for EFL students requires mastery of vocabulary as well. In doing writing also needs a good understanding of vocabulary and sentence structures. Writing was very complex activities to be done, started form drafting to creating. The students at Putra Rifara Vocational School also found some difficulties in learning writing. Mistakes always appeared in doing the task such as grammatical errors, and punctuations. The students also had obstacle in expressing their thought on the paper. The purpose of this research was to obtain empirical evidence about the effect of short video on students' writing procedure text. Quantitative method with quasi-experimental was applied in this study. The sample of this research was eleventh grade students at Putra Rifara Vocational School Kabupaten Tangerang. The purposive sampling was implemented in this research. The total samples were 52 students form two classes (control and experiment class). In the control class consists of 23 students and the experiment class consists of 29 students. The instrument used in this paper was essay. The data was analysed by using SPSS. The result showed that the experimental class got the highest score compared to the control class. Moreover, the result of interview also showed positive respond from the students after learning writing procedure text by using short video. It can be concluded that there was a significant effect of the use short video in improving students’ writing procedure texts for eleventh grade at Putra Rifara Vocational School in Kabupaten Tangerang